Evaluation of the effect of various cryoprotectants on the resistance of canine erythrocytes to mechanical stress - Hrebeniuk, Karyna; Denysova, Olha (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):247